The Role of the Civil Service Police Unit in Implementing Regional Regulation No. 10 of 2014 concerning the Arrangement of Street Vendors in Ambon City - Hendry Selanno (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
The main problem in this study is "How the Role of Civil Service Police Unit in Implementing Ambon City Regulation No. 10 of 2014 at Ambon City Mardika Market?". This study uses a single variable, which involved 41 respondents by including 3 indicators: (1). The role of Civil service police Unit in controlling street vendors, (2). The role of Civil service police Unit in the supervision of street vendors, (3). The role of Civil service police Unit in enforcing the law against street vendors. The results showed that: the average role of Civil service police Unit in the three indicators, namely: control, supervision, and law enforcement against street vendors was considered to be still not good and showed that the role of Civil service police Unit was not fully in implementing Regulation No.10 of 2014. Problems experienced by Civil service police Unit officers in implementing Regional Regulation No.10 2014 in the Ambon City Mardika market are the number of street vendors is increasing from time to time and also the lack of awareness of street vendors in maintaining environmental cleanliness and also compliance with applicable regulations and the absence of special locations provided by the government for street vendors selling.